Expanding the potential of self-assembled silk fibroin as aerogel particles for tissue regeneration - Bernardes, Beatriz G. (2023)
A newly produced silk fibroin (SF) aerogel particulate system using a supercritical carbon dioxide (scCO2)-assisted drying technology is herein proposed for biomedical applications. Different concentrations of silk fibroin (3%, 5%, and 7% (w/v)) were explored to investigate the potential of this technology to produce size- and porosity-controlled particles. Laser diffraction, helium pycnometry, nitrogen adsorption–desorption analysis and Fourier Transform Infrared with Attenuated Total Reflectance (FTIR-ATR) spectroscopy were performed to characterize the physicochemical properties of the material. The enzymatic degradation profile of the SF aerogel particles was evaluated by immersion in protease XIV solution, and the biological properties by cell viability and cell proliferation assays. The obtained aerogel particles were mesoporous with high and concentration dependent specific surface area (203–326 m2/g). They displayed significant antioxidant activity and sustained degradation in the presence of protease XIV enzyme. The in vitro assessment using human dermal fibroblasts (HDF) confirm the particles’ biocompatibility, as well as the enhancement in cell viability and proliferation.